Gut-brain axis: gut dysbiosis and psychiatric disorders in Alzheimer’s and Parkinson’s disease - Denman, Charlotte R.; Park, Sang Myun; Jo, Junghyun (Frontiers in Neuroscience, 2023)
Gut dysbiosis and psychiatric symptoms are common early manifestations of Alzheimer’s disease (AD) and Parkinson’s disease (PD). These diseases, characterised by progressive neuron loss and pathological protein accumulation, impose debilitating effects on patients. Recently, these pathological proteins have been linked with gut dysbiosis and psychiatric disorders. The gut-brain axis links the enteric and central nervous systems, acting as a bidirectional communication pathway to influence brain function and behavior. The relationship triad between gut dysbiosis, psychiatric disorders, and neurodegeneration has been investigated in pairs; however, evidence suggests that they are all interrelated and a deeper understanding is required to unravel the nuances of neurodegenerative diseases. Therefore, this review aims to summarise the current literature on the roles of gut dysbiosis and psychiatric disorders in pathological protein-related neurodegenerative diseases. We discussed how changes in the gut environment can influence the development of psychiatric symptoms and the progression of neurodegeneration and how these features overlap in AD and PD. Moreover, research on the interplay between gut dysbiosis, psychiatric disorders, and neurodegeneration remains in its early phase. In this review, we highlighted potential therapeutic approaches aimed at mitigating gastrointestinal problems and psychiatric disorders to alter the rate of neurodegeneration. Further research to assess the molecular mechanisms underlying AD and PD pathogenesis remains crucial for developing more effective treatments and achieving earlier diagnoses. Moreover, exploring non-invasive, early preventive measures and interventions is a relatively unexplored but important avenue of research in neurodegenerative diseases.